(The use of citrus Leaves as an Ingredient for Instant Noodle) - Salya Sait; Enny Hawani Lubis (Balai Besar Industri Agro, 1991)
The use of volatile leaf oil as well as dried, powdered leaf extract of citrus hystrix DC leaves in vegetable oil as flavoring material for instant noodle has been investigated.For this purpose,the volatile leaf oil was made finely powdered via two kinds of fixation procces involving the use of free-flowing microcrys-talline cellulosepowder as flavor absorbant,sorbitol and sucrose prior to incorporation into the food.Meanwhile a flavoring material in the form of dried,pewderedleaf exract in vegetable oil was also prepared.The results of sesory evaluation of the food using the triangle differential test method concluded that the added flavoring in the form of sorbitol-fixative was of the most preferable one,on the countary, the leaf extract in vegetable oil seemed to be hardly wanted due two flavor-decommposition and off-flavor from the oil during strorage;and the preferable cocentration of flvor in the noodles prepared for ready-to-eat was around 56 ppm.